TRANSPOR IODIN MELALUI MEMBRAN KLOROFORM DENGAN NATRIUM TIOSULFAT SEBAGAI FASA PENERIMA DALAM TEKNIK MEMBRAN CAIR FASA RUAH - -, Refinel; Mustafa, Djufri; Fitriani, Reni (Universitas Andalas, 2015)
Iodine transport throught bulk liquid membrane technique consist of 10 mL I2/KI 4x10-3 N solution as donor phase, 20 mL Na2S2O3 0.02 N solution as reagent striping in acceptor phase, and 30 mL chloroform as membrane phase. Technical operation use magnetic stirring at 100 rpm. Concentration of iodine in donor phase and acceptor phase determined by Spectrophotometer UV-Vis Î» max at 567 nm. The results concluded that the optimum conditions of iodine transport 4 x 10-3 N with pH 7 in donor phase, comparison I2:KI in donor phase (1:5), and a long stirring is 120 minutes. The bulk liquid membrane technique with Na2S2O3 as reagent striping in acceptor phase is potential for iodine transport from donor phase to acceptor phase with 86.71 % of iodine transport. Fluxs values (transport rate) generated by using chloroform membrane of 1.8872 x 10-7 L/cm2.menit-1 at a maximum transport time of 120 minutes.